(untitled) (Alternate Horizons, 2021)
Since the report of the first COVID-19 infected person in South Africa, COVID-19 has moved from being a distant threat to a new reality that resulted in a nationwide lockdown. Though the lockdown was necessary to prepare health facilities for when the country reached its peak, it had a significant negative impact on the economy. In other areas such as the environment, work and education, and the personal lives of South Africans, the consequences have been varied. This article will highlight the positive and negative impact of the past 18 months of lockdown from a South African perspective.